The use of Sanskrit, an ancient language, as a tool to evaluate cleft palate speech problems - Gajiwala Kalpesh (Indian Journal of Plastic Surgery)
Speech is a complex process. The evaluation of speech in an individual with cleft palate is difficult, and the existing classification of phonemes is complicated. Sanskrit, an ancient language, has an arrangement of alphabets that is orderly and scientific and therefore provides a simple means to understand the production of phonemes and memorize them. This article demonstrates the inherent advantage of this arrangement of Sanskrit alphabets to effectively analyze defective cleft palate speech and provides a tool for surgeons to decide a course of action in their routine clinical practice. Improved insight into the speech defect by the surgeon also facilitates better coordination with the speech language pathologist in assessment and treatment of a child with cleft palate.